Integration of Artificial Intelligence in Education: Opportunities, Challenges, Threats and Obstacles. A Literature Review. - Saputra, Indra; Astuti, Murni; Sayuti, Muhammad; Kusumastuti, Dyah (The Indonesian Journal of Computer Science, 2023)
The research background is the rapid development of AI which affects various aspects of education. The purpose of this study is to analyze in depth about the opportunities, challenges, threats and obstacles to the implementation of AI in education. The research method used in this study is semy-systematic literature review. The analysis technique used is a meta-narrative approach that includes the process of identifying, analyzing, recognizing patterns and topic-related themes. The results describe that AI opportunities in education are related to the delivery of learning materials, evaluation, management systems, and educational policy making. Meanwhile, the challenges are related to pedagogy, educational frameworks, and literacy. Threats that arise are related to the security of personal data, character building and educational ethics. Finally, obstacles that arise include the high costs required, limited teacher and professional training schemes in preparing AI competencies, and slow changes in curriculum structure and structural level of education.